Direct production of biodiesel via simultaneous esterification and transesterification of renewable oils using calcined blast furnace dust. (September 2021) - Wang, Yi-Tong; Cong, Wen-Jie; Zeng, Ya-Nan; Zhang, Yu-Qing; Liang, Jing-Long; Li, Jun-Guo; Jiang, Li-Qun; Fang, Zhen
Abstract: Direct production of biodiesel by both esterification and transesterification of renewable oils with acid value (AV) of 9.6–28.9 mg KOH/g using calcined blast furnace dust is studied. Blast furnace dust calcined at 600–700 °C obviously promotes efficient biodiesel production because of the crystal form transformation from lead sulfate particles in dust into active lead oxide, lead sulfide, and lead particles. It is found for the first time that lead oxide, lead sulfide and lead particles can resist saponification from fatty acids to catalyze raw renewable oils to biodiesel with catalytic activity order as follows: lead oxide > lead > lead sulfide > lead sulfate. Biodiesel production process is optimized according to an orthogonal design with biodiesel yield of 92 wt% obtained at AV of 9.6 mg KOH/g (82 wt% after 5 cycles). Biodiesel yield of 84 wt% is achieved at AV of 28.9 mg KOH/g with acidity of 0.18 mmol/g. Calcined blast furnace dust presents potential applications in the production of biodiesel from renewable oils with high AVs. Graphical abstract: Image 1 Highlights: Renewable Jatropha biodiesel is produced by calcined blast furnace dust. Main components PbO, Pb, PbS, PbSO4 resist saponification of free fatty acids. Catalytic activity sequenced as PbO > Pb > PbS > PbSO4 at acid value (AV) 9.6 mg KOH/g. Jatropha biodiesel yield is 92 and 84 wt% at AV of 9.6 and 28.9. Calcined blast furnace dust is cycled 5 times with biodiesel yield of 82 wt%.